H2-powered aviation at airports – Design and economics of LH2 refueling systems. (May 2022) - Hoelzen, J.; Flohr, M.; Silberhorn, D.; Mangold, J.; Bensmann, A.; Hanke-Rauschenbach, R.
Highlights: LH2 demand scenarios at airports until 2050. Component and topology assessment for LH2 refueling systems. Techno-economic optimization of LH2 refueling system for three exemplary airports. Abstract: In this paper, the broader perspective of green hydrogen (H2) supply and refueling systems for aircraft is provided as an enabling technology brick for more climate friendly, H2-powered aviation. For this, two H2 demand scenarios at exemplary airports are determined for 2050. Then, general requirements for liquid hydrogen (LH2) refueling setups in an airport environment are derived and techno-economic models for LH2 storage, liquefaction and transportation to the aircraft are designed. Finally, a cost trade-off study is undertaken for the design of the LH2 setup including LH2 refueling trucks and a LH2 pipeline and hydrant system. It is found that for airports with less than 125 ktLH2 annual demand a LH2 refueling truck setup is the more economic choice. At airports with higher annual LH2 demands a LH2 pipeline & hydrant system can lead to slight cost reductions and enable safer and faster refueling. However, in all demand scenarios the refueling system costs only mark 3 to 4% of the total supply costs of LH2. The latter are dominated by the costs for green H2 produced offsite followed by the costs for liquefaction of H2 at an airport. While cost reducing scaling effects are likely to be achieved for H2 liquefaction plants, other component capacities would already be designed at maximum capacities for medium-sized airports. Furthermore, with annual LH2 demands of 100 ktLH2 and more, medium and larger airports could take a special H2 hub role by 2050 dominating regional H2 consumption. Finally, technology demonstrators are required to reduce uncertainty around major techno-economic parameters such as the investment costs for LH2 pipeline & hydrant systems.